The Influence of Competency, Compensation, and Commitment on Employee Performance in the National Land Agency of the Labuhanbatu Regency - Nasution, Naga Mulia; Siregar, Zulkifli Musannip Efendi; Harahap, Aziddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research was conducted at the National Land Agency of Labuhanbatu Regency, to analyze the influence of competency, compensation, and commitment on employee performance. This research uses quantitative methods, with several analytical techniques such as classical assumption tests, multiple linear regression tests, hypothesis tests, and coefficient of determination tests. The results of this research show that all independent variables have a positive and significant influence on the dependent variable, this is proven through tests and F tests on the data in the research. The results of the t-test show that competency (X1) has a value of tcount (6.72) > ttable (1.66), which means Ha is accepted and Ho is rejected. Meanwhile, the significant value is smaller than the probability value of 0.05 or the significant value of 0.000 <0.05. Thus, it can be concluded that the competency variable (X1) has a positive and significant effect on employee performance. Compensation (X2) has a value of tcount (5.01) > ttable (1.66) which means Ha is accepted and Ho is rejected. Meanwhile, the significant value is smaller than the probability of 0.05 or 0.000 < 0.05. It can be concluded that compensation (X2) has a positive and significant effect on employee performance. Commitment (X3) has a value of tcount (12.28) > ttable (1.66) which means Ha is accepted and Ho is rejected, while the significant value is smaller than the probability of 0.05 or 0.000 < 0.05. Therefore, commitment (X3) has a positive and significant effect on employee performance. The results of the F test show that the Fcount value is 90.60 > Ftable 2.71 with a significance value of 0.000 < 0.05. From these results, it can be concluded that competency (X1), compensation (X2), and commitment (X3) simultaneously have a positive and significant effect on employee performance (Y).